Soleus push-ups and walking two to fifteen minutes after a meal boost metabolism and regulate blood glucose levels - Trakulrungsi, Chatchai (Journal of Current Science and Technology, 2023)
Diabetes is a leading cause of disease and death in the United States (National Health and Nutrition Examination Survey, 2015-2016). According to the National Diabetes Statistics Report (2020), among the overall US population, crude estimates for 2018 were: 34.2 million people of all ages—or 10.5% of the US population—had diabetes; 34.1 million adults aged 18 years or older—or 13.0% of all US adults—had diabetes; 7.3 million adults aged 18 years or older who met laboratory criteria for diabetes were not aware of or did not report having diabetes. This number represents 2.8% of all US adults and 21.4% of all US adults with diabetes. The percentage of adults with diabetes increased with age, reaching 26.8% among those aged 65 years or older. Risk factors for diabetes-related complications include smoking (based on a self-report). Tobacco use was based on self-reported current cigarette smoking or serum cotinine level >10 ng/mL. The former cigarette smoker was based on both 1) no current tobacco use and 2) a history of smoking at least 100 cigarettes in a lifetime), overweight and obesity (body mass index of 25.0–29.9 kg/m2 (overweight), 30.0–39.9 kg/m2 (obesity), or 40.0 kg/m2 or higher (extreme obesity) calculated from measured values of height and weight), physical inactivity (based on a self-report of less than 10 minutes per week of moderate or vigorous activity in each of the physical activity categories of work, leisure time, and transportation), high blood pressure (based on average measured systolic blood pressure of 140 mmHg or higher or the average diastolic blood pressure of 90 mmHg or higher or self-reported current use of prescription medication for high blood pressure), high cholesterol (was calculated as measured total cholesterol level minus HDL cholesterol level). A non-HDL cholesterol value of 130 mg/dL is roughly equivalent to an LDL level of 100 mg/dL, which indicates an increased risk of diabetes-related complications and eligibility for statin therapy), A1C (was classified based on measured glycated hemoglobin), with values higher than 9% indicating poor glycemic control (American Diabetes Association, 2019; Centers for Disease Control and Prevention. National Diabetes Statistics Report, 2020).